Analysis of factors: Prevalence and determinants of anaemia among pregnant women in Mimika, Indonesia - Desty Damayanti; Yenny Puspitasari; Indasah Indasah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anemia in pregnant women remains a chronic issue in Indonesia, with a prevalence of 48.9% based on the 2018 Basic Health Research. A preliminary study at Atuka Health Center, Mimika Regency, found that 4 out of 7 pregnant women had anemia. Purpose: To analyze the factors influencing the incidence of anemia in pregnant women at Atuka Community Health Center, Mimika Regency. Method: This observational analytic study used a cross-sectional design with simple random sampling. The sample included 101 multigravida pregnant women. Independent variables were gestational age, pregnancy spacing, and Fe tablet compliance; the dependent variable was anemia incidence. Logistic regression was used for analysis. Results: Gestational age (p = 0.013), pregnancy spacing (p = 0.022), and Fe tablet compliance (p = 0.005) significantly influenced anemia incidence. Conclusion: Gestational age, pregnancy spacing, and compliance with Fe tablet consumption significantly influence the incidence of anemia. Compliance with Fe tablet consumption is the most influential factor (OR = 4.320).